Corporate Sustainability Reporting and Financial Performance of Oil and Gas Industry in Nigeria - Fineman Gbenekeme Moscow; Ebiaghan Frank Orits (Review of International Economic, Taxation, and Regulations, 2025)
This study explores the relationship between corporate sustainability reporting and key financial metrics such as Return on Assets (ROA), Return on Equity (ROE), Return on Capital Employed (ROCE), and Tobin’s Q for oil and gas companies listed on the Nigerian Exchange Group (NGX). An ex-post facto research design was employed. As of December 31, 2023, the research sample consisted of 15 oil and gas companies that were publicly listed. By using purposeful sampling methods, 5 companies were not included in the study due to missing information, leaving a total of 10 companies in the final sample. Regression analysis was conducted using STATA version 16.0. The aim was to investigate the impact of corporate sustainability reporting on important financial performance indicators. The findings indicate no significant relationship between sustainability reporting and ROA, ROE, or ROCE. However, a significant positive relationship was observed between corporate sustainability reporting and Tobin’s Q. The study concludes that although sustainability reporting does not appear to impact accounting-based performance measures (ROA, ROE, ROCE), it is positively associated with market-based performance (Tobin’s Q) among listed oil and gas firms in Nigeria. This suggests that sustainability practices may influence investor perception and market valuation more than internal financial outcomes.